Optimized cartilage visualization using 7-T sodium ((23)Na) imaging after patella dislocation - Widhalm, Harald K.; Apprich, Sebastian; Welsch, Götz; Zbyn, Stefan; Sadoghi, Patrick; Vekszler, György; Hamboeck, Martina; Weber, Michael; Hajdu, Stefan; Trattnig, Siegfried (Knee Surgery Sports Traumatology Arthroscopy, 2014)
Retropatellar cartilage lesions often occur in the course of recurrent patella dislocation. Aim of this study was to develop a more detailed method for examining cartilage tissue, in order to reduce patient discomfort and time of care.For detailed diagnosing, a 7-T MRI of the knee joint and patella was performed in nine patients, with mean age of 26.4 years, after patella dislocation to measure the cartilage content in three different regions of interest of the patella. Axial sodium ((23)Na) images were derived from an optimized 3D GRE sequence on a 7-T MR scanner. Morphological cartilage grading was performed, and sodium signal-to-noise ratio (SNR) values were calculated. Mean global sodium values and SNR were compared between patients and volunteers.Two out of nine patients showed a maximum cartilage defect of International Cartilage Repair Society (ICRS) grade 3, three of grade 2, three of  grade 1, and one patient showed no cartilage defect. The mean SNR in sodium images for cartilage was 13.4 ± 2.5 in patients and 14.6 ± 3.7 in volunteers (n.s.). A significant negative correlation between age and global sodium SNR for cartilage was found in the medial facet (R = -0.512; R (2) = 0.26; p = 0.030). Mixed-model ANOVA yielded a marked decrease of the sodium SNR, with increasing grade of cartilage lesions (p < 0.001).Utilization of the (23)Na MR imaging will make earlier detection of alterations to the patella cartilage after dislocation possible and will help prevent subsequent disease due to start adequate therapy earlier in the rehabilitation process. LEVEL OF EVIDENCE: II.
EVALuna2:15818